Antiviral activities of ellagitannins against bovine herpesvirus-1, suid alphaherpesvirus-1 and caprine herpesvirus-1 - Neli Vilhelmova-Ilieva , Ivo Sirakov , Remi Jacquet , Stephane Quideau, Angel S. Galabov (African Journal of Pig Farming, 2022)
In vitro antiviral activity of three ellagitannins - castalagin, vescalagin and grandinin was investigated against replication of three of the most common herpes viruses infecting animals, namely bovine herpesvirus-1 (BoHV-1), suid alphaherpesvirus-1 (SuHV-1), and caprine herpesvirus-1 (CapHV-1). The cytopathic effect inhibition test via the neutral red uptake assay in Madin-Darby bovine kidney (MDBK) cell culture was applied. The highest activity was demonstrated by castalagin followed by vescalagin against replication of SuHV-1, strain A2, with selectivity index values of 336.8 and 309, respectively, which are close to that of acyclovir (SI = 540). The activity of grandinin against the replication of SuHV-1 A2 strain (SI = 40.8) as well as the activity of all three substances against the replication of BoHV-1 strain K22 was lower but still significant (castalagin SI = 45; vescalagin SI = 42.5; grandinin SI = 32.3). Against the E/CH strain of CapHV-1, the three ellagitannins showed a moderate to weak activity: Castalagin SI = 19.3, vescalagin SI = 18.8, grandinin SI = 11.8. The results obtained characterize compounds tested as perspective antivirals.